The Roles of Siglec7 and Siglec9 on Natural Killer Cells in Virus Infection and Tumour Progression. (6th April 2020) - Zheng, Yayun; Ma, Xue; Su, Dongmei; Zhang, Yue; Yu, Lin; Jiang, Fangfei; Zhou, Xue; Feng, Ying; Ma, Fang
Abstract : The function of natural killer (NK) cells, defending against virus infection and tumour progression, is regulated by multiple activating and inhibiting receptors expressed on NK cells, among which sialic acid-bind immunoglobulin-like lectins (Siglecs) act as a vital inhibitory group. Previous studies have shown that Siglec7 and Siglec9 are expressed on NK cells, which negatively regulate the function of NK cells and modulate the immune response through the interaction of sialic acid-containing ligands. Siglec7 and Siglec9 are very similar in distribution, gene encoding, protein sequences, ligand affinity, and functions in regulating the immune system against virus and cancers, but differences still exist between them. In this review, we aim to discuss the similarities and differences between Siglec7 and Siglec9 and analyze their functions in virus infection and tumour progression in order to develop better anti-viral and anti-tumor immunotherapy in the future.